METAMORFOSES TEÓRICAS E PRÁTICAS DO ÉTUDE, NA PERSPECTIVA DE ANATÓLI VASSÍLIEV - Fritsch de Almeida, Marcus Vinicius (O Percevejo Online, 2016)
RESUMOA compreensão da prática pedagógica e artística de Anatóli Vassíliev passa primeiro pelo entendimento do “método de análise através da ação”, que foi transmitido ao diretor-pedagogo pela sua mestra Maria Knebel. O método é denominado por Anatóli Vassíliev de Étude, e a partir dele, o diretor desenvolveu uma série de variantes que resultaram, na sua prática pedagógica, na elaboração das estruturas: psicológica e lúdica.Palavras-Chave: Anatóli Vassíliev; Maria Knebel; Étude.ABSTRACTUnderstanding the educational and artistic practice of Anatoly Vasilyev first passes through the understanding of the “method of analysis through action”, which was transmitted to the Director-pedagogue by his mistress Maria Knebel. The method is called by Anatoly Vasilyev of Étude, and from it, the director developed a number of variants that resulted in their teaching, the preparation of the structures: psychological and playful.Keywords: Anatoly Vasilyev; Maria Knebel; Étude.